Selective extension of cerebral vascular calcification in an autopsy case of Fahr's syndrome associated with asymptomatic hypoparathyroidism. Issue 5 (30th August 2021) - Iwase, Tamaki; Yoshida, Mari; Iwasaki, Yasushi; Suzuki, Shugo; Yabata, Hiroyuki; Koizumi, Ryuichi; Moriyoshi, Hideyuki; Yazawa, Ikuru
Abstract : We report an autopsy case of Fahr's syndrome in an 85‐year‐old woman associated with asymptomatic hypoparathyroidism. The patient was diagnosed as having brain calcification at 65 years of age. She developed mild dementia at 75, parkinsonism at 76, and severe dementia at 82. Computed tomography revealed extensive, symmetric intracranial calcification, involving both sides of the basal ganglia and cerebellar dentate nuclei, and severe cerebral atrophy that developed afterwards. A neuropathological examination revealed intracranial calcification, particularly in the wall of the arterioles and capillaries having numerous calcium deposits. Severe vascular calcification and severe neuronal loss without α‐synuclein accumulation were found in the substantia nigra. There were high‐level neuropathological changes indicative of Alzheimer's disease. Although the colocalization of calcium and amyloid‐β deposits in the same arterial wall was rare, both of them were located in a similar layer of the arterial wall. The vascular calcification in the basal ganglia spread continuously through the corona radiata into the selective cerebral areas along the medullary arteries, but did not involve the corpus callosum or insular region. Stone formation was observed at the corona radiata adjacent to the superolateral angles of the lateral ventricles. We hypothesized that there would be a stereotypical extension pattern of vascular calcification related to the arrangement of penetrating arteries in Fahr's syndrome.